EFEKTIVITAS IMPLEMENTASI E-COURT TERHADAP AKSES KEADILAN DI PENGADILAN AGAMA PONTIANAK - Muhamad Arief Padilah; Moh. Fadhil; Husnun Nahdhiyyah (Al-Aqad, 2025)
The objectives of this study are to determine: 1) the implementation of the e-court system at the Pontianak Religious Court; 2) to examine factors affecting access to justice in the implementation of the e-court at the Pontianak Religious Court.  The research method used by the researcher is descriptive-qualitative with a field research type and uses a normative-empirical approach. Data was obtained from two sources, namely primary data sources in the form of structured interviews conducted with the junior clerk for law, the e-court administrator, and litigants who did not use the e-court, regarding the data needed to support this research. And secondary data sources in this study were obtained by reading and studying documents relevant to this research, such as archived case documents, and through other media sourced from literature and related data. The results of this study indicate that the e-court system implemented at the Pontianak Religious Court has brought about a significant transformation in judicial administration, electronically integrating processes from registration to court hearings. Factors that influence access to justice include crucial challenges, such as the digital divide, which encompasses limited access to devices and the internet, as well as a lack of technological literacy among some members of the public.